2007
DOI: 10.1103/physreva.75.032520
|View full text |Cite
|
Sign up to set email alerts
|

Extreme-ultraviolet spectroscopy of highly charged xenon ions created using an electron-beam ion trap

Abstract: Extreme-ultraviolet spectra of xenon ions have been recorded in the 4.5 to 20 nm wavelength region using an electron beam ion trap and a flat field spectrometer. The electron beam energy was varied from 180 eV to 8 keV and radiation from charge states Xe 6+ to Xe 43+ was observed. Our measured wavelengths were compared to atomic structure calculations using the Cowan suite of codes. We have measured seventeen previously unreported features corresponding to transitions in Xe 35+ through to Xe 41+ with estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 37 publications
9
50
0
Order By: Relevance
“…Other pertinent EBIT parameters in this experiment are a 220 V trap depth, 2.7 T magnetic flux density, 4 s trap reloading period, and < 2×10 −3 Pa injected gas reservoir pressure (P1, outer chamber of gas injector, see Ref. [8] for gas injector description; in the present work, the diameter of the injector aperture was 3/16 inch, and the inner diameter of the nozzles were 1/8 inch) on a nominal background pressure inside the ion trap of < 5×10 −9 Pa. For the present experiment, the tungsten atoms were injected into the plasma by a metal vapor vacuum arc (MEVVA) ion source [10]. The MEVVA uses eight cathodes, any one of which can be quickly selected without disturbing any other experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Other pertinent EBIT parameters in this experiment are a 220 V trap depth, 2.7 T magnetic flux density, 4 s trap reloading period, and < 2×10 −3 Pa injected gas reservoir pressure (P1, outer chamber of gas injector, see Ref. [8] for gas injector description; in the present work, the diameter of the injector aperture was 3/16 inch, and the inner diameter of the nozzles were 1/8 inch) on a nominal background pressure inside the ion trap of < 5×10 −9 Pa. For the present experiment, the tungsten atoms were injected into the plasma by a metal vapor vacuum arc (MEVVA) ion source [10]. The MEVVA uses eight cathodes, any one of which can be quickly selected without disturbing any other experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%
“…Wavelength calibration was performed using highly charged neon lines (Ne V-VIII), xenon lines (Xe XLI-XLII), barium lines (Ba XLIII-XLIV), oxygen lines (O V-VI) and iron lines (Fe XXIII-XXIV) [5,7,11,63,64], as described in this section. Neon and carbon dioxide gases were injected into the EBIT as neutral atoms from the gas injection setup described by Fahy et al [2], with the injection pressure normally on the order of 10 −3 Pa. Iron ions were loaded from the MEVVA ion source. Small amounts of barium and xenon ions are always present in the trap as heavy ion contaminants from the electron gun and the ion pumps.…”
Section: Wavelength Calibrationmentioning
confidence: 99%
“…In order to reduce the influence of unresolved satellite lines, one effective method is to further decrease the density of the plasma, resulting in a lower population in highly excited states. Fahy et al [5,11] recorded EUV spectra in the 4.5-to 20-nm wavelength region from Xe ions at the Electron Beam Ion Trap at NIST [12], which operates with electron densities in the range of 10 13 -10 14 cm À3 or even lower. Emissions from Xe 6+ to Xe 43+ were observed.…”
Section: Introductionmentioning
confidence: 99%